The Impact of Direct Benefits of Control on the Price Informative Value of Voluntary Information Disclosure: An Empirical Study of the Iranian Public Listed Companies - Gholamreza Zandi; Alireza Shahabi (Journal of Accounting and Management Information Systems (JAMIS), 2012)
This paper seeks whether the voluntarily information disclosed by public companies listed on the TSE where the institutional blockholders possess the Direct Benefit of Control (DBC) is useful and relevant information as a proxy for presenting true financial picture. We assumed that the relevant voluntary disclosure indicates more transparency. We chose the annual reports of all public companies listed on the main board of TSE in 2009. Two types of indices were constructed, an index for the extent of voluntary disclosure (VD), and an index for the price informative voluntary disclosure (PID). The results show that the institutional blockholders meet the needs of market for information by disclosing a lot of information (VD) but with less-relevant content in order to cover up their perks' consumptions. The blockholders would like to show the market is efficient with no information asymmetry however such transparency is not genuine. This paper may contribute to the literature whereas the presence of blockholders shall increase the extent of voluntary disclosure (VD) but the transparency may decline.
Keywords: M41; G17; 650; Price informative; voluntary disclosure; direct benefits of control; blockholders